HERMENEUTIK FEMINIS TERHADAP NARASI KITAB RUT 1:16; KARAKTER, PERKATAAN TINDAKAN DAN KESETIAAN - Ayub Rusmanto; Mozes Huwae (STT Saint Paul Bandung, 2022)
This paper intends to find out Ruth is a woman of character and integrity in various perspectives in terms of words, actions and loyalty as a daughter-in-law and a foreigner (Moab), (Ruth 1:16). With the struggles and challenges of life's journey as Naomi's daughter-in-law and a foreigner (Moab), Ruth remains committed in words and actions that reflect a person of integrity. The author executes Ruth 1:16 as a hermeneutic validation text and the inspiration for the exposition. The method used in writing this paper is a descriptive qualitative method with a correlated library, literature, published journal approach to examine the subject matter to explore the feminist hermeneutics of the narrative of the Book of Ruth: characters, words, actions and loyalty. This paper presents a theological study of women's contributions through feminist hermeneutics, while still upholding the respect and authority of the Bible. By reflecting on the feminist hermeneutics of the narrative of the Book of Ruth: character, words, actions and fidelity to the role of women in society, ministry in the church and life in the home.